Songs of wisdom and circles of dance : hymns of the Satpanth Ismāì̄lī Muslim saint, Pīr Shams - Kassam, Tazim R. (McGill studies in the history of religions., 1995)
Coursing through cultures and time, tuneful verse has given moving expression to the human longing for the divine. As poetry strung on sweet melodies, hymns bear testimony to the religious life of the devout, and to the inspiring teachings of minstrels and saints. Such is the ginan tradition of the Satpanth Ismailis, Indian successors of the Fatimid and Nizari Ismaili sect of the Shiah Muslims.